2017
DOI: 10.2471/blt.16.189399
|View full text |Cite
|
Sign up to set email alerts
|

Integrated morbidity management for lymphatic filariasis and podoconiosis, Ethiopia

Abstract: ProblemLymphatic filariasis and podoconiosis are the major causes of tropical lymphoedema in Ethiopia. The diseases require a similar provision of care, but until recently the Ethiopian health system did not integrate the morbidity management.ApproachTo establish health-care services for integrated lymphoedema morbidity management, the health ministry and partners used existing governmental structures. Integrated disease mapping was done in 659 out of the 817 districts, to identify endemic districts. To inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 5 publications
0
34
0
1
Order By: Relevance
“…LF and podoconiosis morbidity management and disability prevention (MMDP) programmes largely consist of limb hygiene and self-care activities, which are paramount to alleviate suffering and to reduce the occurrence of ADLAs [37]. It is pragmatic, cost-effective and efficient to integrate the LF and podoconiosis MMDP programmes where possible [38].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LF and podoconiosis morbidity management and disability prevention (MMDP) programmes largely consist of limb hygiene and self-care activities, which are paramount to alleviate suffering and to reduce the occurrence of ADLAs [37]. It is pragmatic, cost-effective and efficient to integrate the LF and podoconiosis MMDP programmes where possible [38].…”
mentioning
confidence: 99%
“…This study, therefore, aimed to determine the socio-economic impact on caregivers for patients with leg lymphoedema in Ethiopia, where an estimated 5.6 million individuals are at risk of LF and 34.9 million individuals are at risk of podoconiosis [38]. A cross-sectional survey in a co-endemic district highlighted caregiver socio-demographic characteristics, types of care provided, QoL, and productivity, with key indicators compared in the presence and absence of patients' ADLAs.…”
mentioning
confidence: 99%
“…While integrated approaches to the case management of skin NTDs have been implemented in co-endemic areas, few health systems have documented actual experiences of implementation [25]. A case study in Ethiopia reported the managerial feasibility of integrating morbidity management of tropical lymphedema caused by lymphatic filariasis (LF) and podoconiosis [26]. Patient experiences of integrated care for leprosy and BU in Cote d'Ivoire [25], LF and leprosy in Nepal [27], and multiple skin NTDs in Liberia [18] have been explored in community settings, but studies investigating the social experience of integrated case management in facility settings are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Areas where the LF programme has already advanced, the existing platform and programme activities such as the transmission assessment surveys (TAS) can be used to integrate podoconiosis mapping. Once the mapping is completed integrated morbidity movement services can be provided to all cases, as has been found to be feasible in Ethiopia 62 .…”
Section: Discussionmentioning
confidence: 99%